Step-Up Co-working Center - Ibrahimova, Nigar (ADA University, 2020)
According to a list published by the Global Startup Ranking in 2019, Azerbaijan ranked 47 globally and as the third best CIS country for launching startups. There were made 200 startups in Azerbaijan last year, therefore in order to support startup ecosystem and help young people to implement their ideas series of measures had been taken by the Azerbaijani Government. Those actions include the establishment of the State Fund for Development of Information Technologies which is involved in providing investment, the establishment of a joint consortium with the participation of the Innovation Agency under the Ministry of Transport, Communications, High Technologies and AzInTelecom LLC. Taking into consideration the great involvement of Azerbaijani youth in startup ecosystem and enhancement of governmental support on this issue nowadays, I have decided on launching such a business which will help youngsters to produce and develop more and more ideas, nevertheless not only the youth but also employees and freelancers as well. Co-working spaces are getting more and more popular every day. Majority of the biggest companies (Uber, Spotify, Instagram) prefers co-working spaces as a working place. This centers help professionals, new entrepreneurs, freelancers and students to work in more cozy atmosphere, to save their time, to help to create a professional network and get support from the people they work with and it definitely helps their business to grow faster. Additionally, students prefer to study in co-working centers rather than at home since there are less distracting factors, moreover student organizations also prefer to organize their seminars and workshops in such type of offices. The company to start is called “Step-up Co-working center”. The main services it will provide are: renting working desks/rooms, high-speed internet, conference rooms for 8-10 people, small rooms for face-to-face interviews , big event room with capacity of hosting 80 people, free coffee and snacks, open space for individuals, and most importantly a community of like-minded people. How I came up with this idea? I realized that there are only few co-working centers in Baku despite it gets more demanded everyday (according to my survey) and as I researched price strategies of all potential rivals (according to my market analysis) it has been revealed that there is no golden mid rule, thus I will provide this mid with better service and marketing strategy. The primary objective is not getting a profit as soon as possible, instead to become the most demanded, popular and preferable co-working center in the city. Our target customers are students, entrepreneurs, freelancers and youth organizations. Freelancers who do not have enough budget to rent an office and who want to enhance their professional network, students who prefer to study in more relaxing atmosphere, employees (HR managers e.g), who do not have an appropriate place to establish interviews or meetings, finally youth organizations who organize vary workshops and events on a weekly basis may make use of our center. To launch this business initially I would need to invest 20.000 AZN, which will cover office rent, salaries of staff, interior & design expenses, equipment & furniture, communal expenses, taxes, and most importantly marketing expenses.
Keywords: Business; Co-working Center -- Azerbaijan.; Customer satisfaction -- Azerbaijan.; Online services -- Azerbaijan.